2023
DOI: 10.3389/fnins.2023.1160243
|View full text |Cite
|
Sign up to set email alerts
|

Investigating behavioral phenotypes related to autism spectrum disorder in a gene-environment interaction model of Cntnap2 deficiency and Poly I:C maternal immune activation

Abstract: IntroductionAutism Spectrum Disorder (ASD) has been associated with a wide variety of genetic and environmental risk factors in both human and preclinical studies. Together, findings support a gene-environment interaction hypothesis whereby different risk factors independently and synergistically impair neurodevelopment and lead to the core symptoms of ASD. To date, this hypothesis has not been commonly investigated in preclinical ASD models. Mutations in the Contactin-associated protein-like 2 (Cntnap2) gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Finally, they shed some light on the phenotypic heterogeneity associated with Cntnap2 heterozygous mutation, suggesting that mutations of this gene may constitute a causal factor for specific psychiatric pathology only and exclusively when associated with specific environmental factors, such as prenatal immune activation (12) or early-life stress. (B-F) Left panels: charts summarizing the quantification of the main effect of the covariates included in the model; Right charts: depict the results of multiple comparisons for the given outcome measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, they shed some light on the phenotypic heterogeneity associated with Cntnap2 heterozygous mutation, suggesting that mutations of this gene may constitute a causal factor for specific psychiatric pathology only and exclusively when associated with specific environmental factors, such as prenatal immune activation (12) or early-life stress. (B-F) Left panels: charts summarizing the quantification of the main effect of the covariates included in the model; Right charts: depict the results of multiple comparisons for the given outcome measure.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that, the phenotypic heterogeneity related to CNTNAP2 haploinsufficiency may arise as a consequence of the gene-environment interaction, shaping specific phenotypic trajectories in response to early-life experiences occurring during critical stages of neurodevelopment. A previous study explored this possibility by exposing Cntnap2 +/to a prenatal Poly-I:C maternal immune activation, which exacerbates autistic-like behaviors in this model (12). In this work we sought to determine whether an environmental stressor during early-postnatal development may shape behavioral hallmarks associated with a specific CNTNAP2-related conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Haddad et al. found that both MIA and Cntnap2 gene deficiency resulted in similar ASD-like behavioral deficits, but that both independently and synergistically exacerbated ASD-like symptoms in model rats when acted upon together ( 143 ). The opposite result was obtained by Kim et al.…”
Section: Interactions Of Genetics Environment Neural Pathways Neuroin...mentioning
confidence: 99%
“…Partial or full deletion of the neurexin family ASD-risk gene Cntnap2 (contactin-associated protein-like 2) caused genotype-specific effects on adult female locomotor activity and sexindependent reduction in sociability in heterozygous and in PPI in hemizygous adolescent MIA (poly(I:C), GD9.5) offspring (Haddad et al, 2023), underscoring the importance of age, sex, and genetic dose on MIA-induced deficits. The full deletion alone caused increased startle response, hyperactivity, and moderate PPI reduction (exasperated by MIA) across ages.…”
Section: Introduction 30mentioning
confidence: 96%